Review of Smart Services for Tinnitus Self-Help, Diagnostics and Treatments - Kalle, Sven; Schlee, Winfried; Pryss, Rüdiger C.; Probst, Thomas; Reichert, Manfred; Langguth, Berthold; Spiliopoulou, Myra (Frontiers in Neuroscience, 2018)
In the recent years, there has been an increasing interest in the potential of internet- and smartphone-based technologies for the support of tinnitus patients. A broad spectrum of relevant approaches, some in the form of studies, others in the form of market products, have been mentioned in literature. They include auditory treatments, internet-based Cognitive Behavioral Therapy (iCBT), serious games, and questionnaires for tinnitus monitoring. The goal of this study is to highlight the role of existing internet-based and smart technologies for the advancement of tinnitus clinical practice: we consider contributions that refer to treatments and diagnostics, and we include contributions refering to self-help measures. We elaborate on the potential and challenges of such solutions and identify constraints associated to their deployment, such as the demand for familiarity with internet-based services and the need to re-design interactive services so that they fit on the small surface of a smartwatch.